PEMBERDAYAAN MASYARAKAT BERBASIS DESA MANDIRI PANGAN DI DESA MARGOSARI KECAMATAN LIMBANGAN KABUPATEN KENDAL - Yustika Ariani; Achmad Taufiq; Fitriyah . (Journal of Politic and Government Studies, 2016)
Kendal Regency is the one of the regencies in Central Java with high poverty levels. One of the efforts to reduce poverty, issued The Regional Regulation No. 4 of 2011 on Poverty Reduction in Kendal Regency and poverty reduction programs. Based on that Regional Regulation No. 4 of 2011, the main priority of poverty reduction in Kendal Regency is regarding food needs. So, the community empowerment program initiated by the Food Resilience Village programs that aimed for handling of regional food insecurity and poverty. This research focuses on the implementation of the Food Resilience Village programs in Margosari Village, Limbangan Subdistrict, Kendal Regency.The type of research is qualitative analytical descriptive. Data was obtained from the primary and secondary data source, using purposive sampling technique for selecting informants. Data collection techniques used were observation, indepth interviews, and literature / documents.The results showed that the implementation of the community empowerment program based on the Food Resilience Village programs in Margosari Village, Limbangan Subdistrict, Kendal Regency was successful and has entered the stage of independently. This is due to the support and the role of community and village government were pretty good. Although, there are several obstacles factors in the implementation of Food Resilience Village activities, such as lack of human resources, administrative problems, the level of public awareness, and the problems that occur in cattle.The writer gives some advice to District of Kendal’s Government and the society of Margosari Village as beneficiaries Food Resilience Village programs. For local governments in order to further reinforce efforts to reduce poverty and overcome problems that occurred during the implementation of the program. As for the villagers, they have to improve their human resources and skills possessed by, therefore can overcome obstacles in the implementation of the activities, especially the problem of administration.